THE DIFFERENT APPROACHES TO THE TRANSFORMATION OF REACTIVE POWER INTO AN ACTIVE POWER - BATYGIN, YURIY; SHINDERUK, SVITLANA; CHAPLYGIN, EVGEN; FENDRYKOV, DENIS (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The relevance of the development of modern problems of the electric power industry in connection with the depletion of the planet's natural resources is undeniable and initiates the development of new physical and technical solutions with the practical use of known natural phenomena. The method of this work is to propose, justifying the expediency of a possible scheme of a resonant converter of reactive power into activity and conducting an analysis of the electromagnetic processes occurring in them. The proposed schemes combine the presence of resonant parallel and resonant circuit complexes. The difference is in the way they are implemented. For the data of the joint circuit, the feature is the presence of two inductively coupled active-reactive circuits, but different in the ways of creating resonance conditions. For a circuit without an additional power source, it is shown that the successful implementation of resonance conditions is possible by choosing the appropriate element base. For a circuit with an additional source of harmonic voltage, it is shown that for a suitable setting it is possible to completely eliminate the negative influence of the converter circuit on the source of reactive power. Calculations for the experimental model show that with the appropriate selection of the element base, it is possible to obtain a conversion factor of ~ 1.0 with a minimal effect on the current in reactive power sources. Given the calculated ratios, the mathematical apparatus of the theory of electric circuits was used to substantiate the principle possibility of resonant transformation of electrical energy. Thus, methods of calculating the characteristics of transient processes in closed circuits with active-reactive elements. For the first time, with the justification of practical power, we offer the possibilities of the scheme of resonant transformation of reactive power into active power, and an analysis of the electromagnetic processes occurring in them is carried out. The proposed work was initiated by the current needs of the electric power industry, caused by the depletion of natural resources and the rapidly growing needs of the world economy. The results of the work illustrate the practical possibilities of creating real schemes for converting reactive electricity into active electricity.
Keywords: electric power industry; resonant active-reactive electrical circuits; electrical power conversion